Survival Benefit of Intervention Treatment in Advanced Anaplastic Thyroid Cancer. (3rd June 2021) - Kasemsiri, Pornthep; Chaisakgreenon, Pimpika; Vatanasapt, Patravoot; Laohasiriwong, Supawan; Teeramatwanich, Watchareeporn; Thongrong, Cattleya; Ratanaanekchai, Teeraporn; Suetrong, Surapol
Abstract : Background . The management of anaplastic thyroid cancer (ATC) is controversial; thus, proper treatment and prognostic factors should be investigated. Objectives . To compare the survival outcomes of the intervention and palliative treatment in ATC patients. Methods . A hospital-based retrospective study was conducted at a single tertiary university hospital. The medical record charts were retrieved from November 20, 1987, to December 31, 2016. The final follow-up ended by December 31, 2017. The patients' demographic data, laboratory data, clinical presentation, and treatment modality results were analyzed. Results . One hundred twenty-one records were analyzed with a one-year overall survival rate of 3.5% (median survival time: 77 days); however, 16 cases had insufficient data to classify staging and treatment modalities. Therefore, 105 ATC patients (37 with stage IVa, 39 with stage IVb, and 29 with stage IVc disease) were included with a one-year overall survival rate of 4.0% (median survival time of 82 days). Intervention treatment allowed longer median survival times (p < 0.05 ) and a better survival rate (p < 0.05 ). Among the interventional treatment groups, postoperative chemoradiation yielded the longest median survival time (187 days) and the highest survival rate (20%) (p < 0.05 ). The intervention modality allowed a better median survival time at all stages, particularly in stage IVa (p < 0.05 ). Unfavorable prognostic factors were adjusted for in a multiple Cox regression model showing that significant factors included age ≥65 years (hazard ratio HR: 2.57), palliative treatment (HR: 1.85), and leukocytosis ≥10, 000 cells/mm 3 (HR: 2.76). Conclusions . Intervention treatment provided a better survival outcome in all stages, particularly in stage IVa, with a significantly better median survival time. Among interventional treatments, postoperative chemoradiation led to the longest survival rate, suggesting that this treatment should be considered in ATC patients with resectable tumors and no poor prognostic factors, such as older age and leukocytosis.